FORECASTING OF FOREIGN DIRECT INVESTMENTS INTO THE REGIONS OF RUSSIAN FEDERATION - Lilia V. Matraeva (Статистика и экономика)
This article is dedicated to the problem of forecasting of Foreign Direct Investments (later in article - FDI) into the regions of Russian Federation. Assessment of FDI forecasted levels is done using not only classical forecasting methods (e.g. ARIMA) but with modern methods used by researches currently - neural networks.Comparative analysis of efficiency of above mentioned methods is done in this article as well. Assessment is done on when modern forecasting methods are more suitable than classical ones which is illustrated on real life examples.